The impact of hallyu on Korean food consumption: the role of imitation intention / Nur Nadhirah Zaini ... [et al.] - Zaini, Nur Nadhirah; Mohtar, Tini Maizura; Awang Razli, Izyanti; Abdul Adis, Azaze-Azizi (Faculty of Hotel & Tourism Management, Universiti Teknologi MARA, 2024)
Due to its unique flavour, health benefits, and cultural value, Hanshik has grown to be known and loved around the entire globe. This study explains how the attitudes towards Korean culture, normative social influence, and perceived behaviour control the intention to consume Korean food and further explores how consumers’ imitation intention of Korean entertainment is positively associated with consumption intention. The study subjects are based on primary data collected from 569 Malaysian consumers. Convenience sampling was the method used in sampling. The analysis was conducted in two stages, the first of which involved testing the measurement model to ensure the validity and reliability of this study, and the second of which involved using the (PLS-SEM) to understand the significant impact of the predictors on intention to consume Korean cuisine Hanshik. The results show that attitude towards Korean culture, normative social influence, and perceived behavioural control are highly influenced by the intention to consume Hanshik. Additionally, this study looked at the role of imitation intention by using the Theory of Imitation and found the imitation intention has a positive impact on Korean food consumption intention. This research shows that consumers and marketing professionals promoting Korean food, or other Korean cultural items have improved their understanding of and interest in Korean food due to exposure to Korean entertainment media.